Environment As Risk Factors of Schizophrenia: A Systematic Review - Agustina, L; Arminsih Wulandari, R (KnE Life Sciences, 2019)
Schizophrenia is a costliest mental disorder regarding human suffering and social expenditure. Schizophrenia is a severe mental illness caused by a gene-environment interaction. An environment has an important role in schizophrenia. It is important to know which environmental factor has related to schizophrenia for the prevention and control of schizophrenia. The study was done by using a systematic review to identify which environmental risk factor and variables associated with schizophrenia. The reviewed articles are from Pro quest, Science Direct, and Scopus database, published on a peer review journal, in English, with human subject, physical and chemical environment factor related with schizophrenia studies. There were 99 articles, and seven selected articles reviewed systematically. An extreme hot ambient temperature, born in winter or early spring, air pollution especially with PM10, PM2,5, SO2 dan NO2 , lead, and tetrachlorethylene exposure had a significant correlation with schizophrenia. Female had higher risk than male. Older age corra elates with the risk of schizophrenia. Urban people have a higher risk than rural people. Further studies required to confirm these correlations. Season of birth and schizophrenia studies for two seasons countries may be required. This study limitations only compared two articles for each environmental factor, and the metal exposure had no comparison. The next studies are necessary to review specific exposure-related schizophrenia with more articles. Keywords: Schizophrenia, Environment, Systematic Review